Spectroscopic analysis of epoxidised jatropha oil (EJO) and acrylated epoxidised jatropha oil (AEJO) - Wong, Jia Li; Aung, Min Min; Lim, Hong Ngee; Md Jamil, Siti Nurul Ain (Universiti Putra Malaysia Press, 2017)
The non-edible seed oil of the Jatropha plant is a renewable and sustainable material to produce vegetable oil-based epoxy and epoxy acrylate as raw polymeric material. The objective of this study is to synthesis Jatropha seed oil-based epoxy and acrylate epoxy resins through conventional methods. An epoxy ring of Epoxidised Jatropha Oil (EJO) was formed through an in-situ epoxidation process using hydrogen peroxide and formic acid as an oxygen donor and oxygen carrier respectively. Acrylated Epoxidised Jatropha Oil (AEJO) was produced by reacting EJO with acrylic acid with the existence of triethylamine and 4-methoxyphenol as a catalyst and inhibitor respectively. The measured oxirane-oxygen content (OOC) of EJO was 4.99%. The acid value of the AEJO was determined at 4.42 mg KOH/g. Both the EJO and AEJO were characterised by FTIR and 1H NMR spectroscopies.